Melanocytic Neoplasms With MAP2K1 in Frame Deletions and Spitz Morphology. (December 2020) - Sunshine, Joel C.; Kim, Daniel; Zhang, Bin; Compres, Elsy V.; Khan, Ayesha U.; Busam, Klaus J.; Gerami, Pedram
Abstract : Abstract: With the advent of better molecular characterization of Spitz melanocytic neoplasms, there has been increasing effort to better understand and describe the relationships between specific driver fusion and/or mutations with the clinical and histomorphological characteristics of the lesions. Structural rearrangements in mitogen activated protein kinase genes have recently been noted to be important in Spitz neoplasms. Only very few reports, however, have described in detail melanocytic tumors with in frame deletions in MAP2K1. Cases in the literature with this aberration have been described as having a diagnosis of Spitz, deep penetrating nevi, or pigmented epithelioid melanocytoma. In this study, we describe a cohort of 6 cases with MAP2K1 activating in frame deletions. The morphologic spectrum of the cases was broad. Common features of these cases include Spitzoid cytomorphology (5/6) cases, prominent melanin pigmentation (4/6) cases, and deep penetrating nevi–like plexiform architecture (3/6) cases. The diagnoses at the time of clinical care of these cases included nevus of Reed (1/6), desmoplastic Spitz tumor (1/6), BAPoma (1/6), deep penetrating melanocytic nevus (2/6), and melanoma (1/6). Clinical follow-up was available in 3 of the 6 cases. None of the patients had a tumor recurrence. This builds on the growing literature to help expand the spectrum of changes associated with Spitzoid melanocytic neoplasms.